Atlantic Water in the Nordic Seas Properties, Variability, Climatic Importance - Walczowski, Waldemar. (GeoPlanet: Earth and Planetary Sciences,, 2014)
The book presents a wide description of hydrographic conditions in the studied area of the Norwegian and Greenland Seas. Variability of the Atlantic Water properties have been presented on the basis of time series obtained from oceanographic measurements performed each summer from 2000 to 2007 by the Institute of Oceanology Polish Academy of Sciences. The warming observed in that period has been described in detail as well as cooling of the Atlantic Water flowing towards the Fram Strait in 2007. Furthermore, concepts regarding multi-branch structure of the West Spitsbergen Current have been presented, types of flows in individual branches as well as variability of the flows. Description of the structure, transports and variability of the sea currents is based mostly on hydrographic measurements and baroclinic calculations. The results confirm a leading role of the ocean in climate shaping and acknowledges the importance of the Thermohaline Circulation for the climate.